1956
DOI: 10.2134/agronj1956.00021962004800020005x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Location, Hybrid, Fertilizer, and Rate of Planting on the Oil and Protein Contents of Corn Grain1

Abstract: SYNOPSISWith 7 corn hybrids at various locations in Virginia, hybrids were more important than growing conditions as a source of variation in oil content; the reverse was true for the effect on protein content. With 3 levels of N, P, and K, and at 10,000 and 16,000 plants per acre, the location, planting rate, and N level all significantly affected protein content. Protein content was significantly higher under drought conditions than under good growing conditions. Highest protein yields occurred with the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
23
0
9

Year Published

1963
1963
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 4 publications
7
23
0
9
Order By: Relevance
“…This agrees with the results from Genter et al (1956), Welch (1969), Jellum et al (1973), and Jellum and Morion (1966). Based on the oil content increase in the population per se, Saratlic (1994) indicated that additive gene effects were the most important types of gene action governing this trait.…”
Section: Effect Of Selection On Genetic Parameterssupporting
confidence: 92%
“…This agrees with the results from Genter et al (1956), Welch (1969), Jellum et al (1973), and Jellum and Morion (1966). Based on the oil content increase in the population per se, Saratlic (1994) indicated that additive gene effects were the most important types of gene action governing this trait.…”
Section: Effect Of Selection On Genetic Parameterssupporting
confidence: 92%
“…A aplicação de maiores doses de N aumentou a porcentagem de proteína nos grãos, significativamente em Mococa, em concordância com outros autores (12,17,19,22). Porém, não houve variação desse componente em função de níveis de P 2 0 5 ou K 2 0 (12).…”
Section: -Proteína E Aminoacidosunclassified
“…As poucas referências existentes na literatura dão mais ênfase à influência do nitrogênio. Genter e outros (12) observaram efeitos do nível de fertilidade, localidade, população e híbrido no teor de proteína, enquanto o teor de óleo foi mais afetado pelo híbrido do que pelos outros fatores. Jellum e outros (17) verificaram um aumento de proteína com o aumento da dose de N aplicada, e nenhum efeito no teor de óleo.…”
Section: -Introduçãounclassified
“…Alguns autores têm procurado demonstrar a influência de certos nutrientes sobre o teor de proteína nos grãos de milho (4,5,6). AR-NON (2) apresenta uma revisão sobre o efeito de nutrientes na composição da planta e dos grãos de milho, com alguma ênfase no teor e na qualidade da proteína, com o primeiro influenciado pelo nitrogênio, potássio, fósfo-ro e interação nitrogênio x enxofre.…”
Section: Introductionunclassified